Designing Expert System for Diagnosing Cancer with Forward Chaining Method - Keith Francis Ratumbuisang; Yosua Fitsgerald Ratumbuisang; Dedi Sorongan (Universitas Sam Ratulangi, 2021)
Abstract - This study aims to produce software in the form of a Cancer Diagnosis Expert System using a system capable of managing the implementation of general disease diagnosis input in humans, namely registration, filling in symptoms of disease, early diagnosis, and given drugs. This research also tested the feasibility level of the software that has been made. The system development method uses the waterfall method with a 4-stage design, namely Analysis, Design, Coding and Testing. Meanwhile, the method of finding / drawing conclusions is the forward chaining method.. Software testing is done through black-box testing, McCall's Quality Factor as an indicator to determine the feasibility of the software with a measurement scale using a Likert scale. Interviews and questionnaires are techniques used to collect data, while data analysis techniques use quantitative descriptive analysis. The web-based expert system for diagnosing rice plant diseases that has been developed has the advantage of ease of access and ease of use. With its web-based features, the expert system for cancer diagnosis that has been built can be used as a tool for diagnosing various types of cancer and can be accessed by anyone.Keywords - Expert System, Cancer Disease, Diagnosis, Forward Chaining